Development of maternal and child health services in the minority communities of Israel - Rebecca Adams (AOSIS, 1981)
TO get to the maternal and child health station in Mahamadia, a Moslem Arab village, you alight from the bus at the foot of Mount Tabor, slide down a hill, and find yourself in a courtyard with children and sheep. Bahija, the practical nurse, greets you and laughs as she tells of the Jewish paediatrician who, because of religious tenets forbidding touching a strange woman, refused to take her helping hand and proceeded to fall all the way. From the entrance shed you are led to two rooms with light coming from the open doors. The rooms are clean with stone floors that are easily washed and with the standard blue and white furniture seen in every Ministry of Health or Kupat Holim (General Sick Fund of the Federation of Labor) station in Israel.